Citizen Participation in the Information Society
XIII, 196 p. 5 illus., 1 illus. in color.
Keywords: This open access book examines how digital technologies are used to promote citizen participation in democratic urban development. It assesses the emergence, use, applicability and functions of digital modes of citizen participation in multiple cities around the world, where political regimes invite ordinary citizens to partake in policy processes through information technologies. The book also explores these initiatives alongside issues of democracy, social justice and power. It is an essential reference for practitioners, policymakers and academics interested in the relationship between citizen participation, technology and urban governance. Sissel Hovik is Professor at Oslo Business School, Oslo Metropolitan University, Norway. G. Anthony Giannoumis is Associate Professor of Universal Design at Oslo Metropolitan University, Norway. Kristin Reichborn-Kjennerud is Senior Researcher at the Work Research Institute, Oslo Metropolitan University, Norway. José Manuel Ruano de la Fuente is Professor in the Department of Political and Administrative Sciences, Complutense University of Madrid, Spain. Ian McShane is Associate Professor at the Centre for Urban Research, RMIT University, Australia. Sveinung Legard is Postdoctoral Fellow at Oslo Business School, Oslo Metropolitan University, Norway.